PERBEDAAN TINGKAT AGRESIVITAS PADA SISWA SMU MUHI YOGYAKARTA BERDASAR POLA ASUH DAN JENIS PEKERJAAN ORANG TUA - Hanif Cahyo Adi Kistoro (Universitas Ahmad Dahlan, 2013)
This research aims at examining the difference of aggressiveness in students Senior High School of First Muhammedan (SMU MUHI) Yogyakarta from parent’s rearings and parent’s jobs. It based on phenomenons, such increase of fights along students, behaviors of students less polite to teachers, and others, especially that occurs in Yogyakarta. It indicated of aggressive behaviour. It may be caused of not right of parent’s rearings, and parent’s rearings has correlation with parent’s jobs. From these phenomenons, reseacher want to investigated about difference of aggressiveness in students Senior High School of First Muhammedan from parent’s rearings (authoritarian, democratic, and permissive) and from parent’s jobs (entrepreneur, official civil servant/PNS, and military) point of view to aggressiveness. Two hypotheses tested are as follows: (a) that there is a difference of agressiveness in students Senior High School of First Muhammedan (SMU MUHI) have parents tendency to authoritatif, democratic, and permissive, and b) that there is a difference of agressiveness in students Senior High School of First Muhammedan (SMU MUHI) have parents as entrepreneur, official civil servant, and military. Subjects of the research include seventy six students of first class and sixty seven students of second class in Senior High School of First Muhammedan (SMU MUHI), Yogyakarta and their parents, totally is one hundred and sixty person. The two instruments administered in data gathering (quantitative data) include parent’s rearings scale for students’ parent (within there was a identity of parent’s job), agressiveness scale for students, and interview (qualitative data). Variance analysis 2-stripes (Anava 2-jalur) were applied to analyze the data. The outcome shows the following: (a) there is a significant difference of three parent’s rearings to bring about aggressiveness with F=366.479, standar error p=0.000, and difference average is: authoritarian=69.344; democratic=79.283; permissive=87.862. (b) there is not a significant difference of three parent’s jobs to bring about aggressiveness with F=0.054, standar error p=0.583, and difference average is: entrepreneur=77.632; official civil servant=76.436; military=76.960. From the result of parent’s rearings appeared that permissive is the most influential from all (authoritarian and democratic) to bring about aggressiveness in students of Senior High School of First Muhhammedan, Yogyakarta, and parent’s rearings hasn’t influence to bring about children’s aggressiveness.